Correlation between pharmacokinetics and pharmacogenetics of Selective Serotonin Reuptake Inhibitors and Selective Serotonin and Noradrenaline Reuptake Inhibitors and maternal and neonatal outcomes: Results from a naturalistic study in patients with affective disorders. (30th November 2020) - Colombo, Anna; Giordano, Francesca; Giorgetti, Federica; Di Bernardo, Ilaria; Bosi, Monica F.; Varinelli, Alberto; Cafaro, Rita; Pileri, Paola; Cetin, Irene; Clementi, Emilio; Viganò, Caterina A.; Dell'Osso, Bernardo
Abstract: Objective: Some studies have linked the use of selective serotonin reuptake inhibitors and selective serotonin and noradrenaline reuptake inhibitors (SSRIs/SNRIs) to the risk of perinatal complications. This study explored the relationship between pharmacokinetics and pharmacogenetics, SSRIs/SNRIs tolerability and effectiveness and maternal and newborn outcomes. Methods: Fifty‐five pregnant women with Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM‐5) diagnoses of affective disorders, treated with SSRIs/SNRIs, were recruited and, during the third trimester, their blood samples were collected for pharmacokinetic and pharmacogenetic analyses. Plasma levels and metabolic phenotypes were then related to different obstetrical and maternal outcomes. Results: The pharmacokinetic data were more stable for Sertraline, Citalopram, and Escitalopram compared to other molecules (p = 0.009). The occurrence of postnatal adaptation syndrome onset was associated with higher plasma levels for Sertraline (median at delivery: 16.7 vs. 10.5 ng/ml), but not for fluoxetine and venlafaxine. Finally, the subgroup within range plasma concentrations had less blood loss than the below range subgroup (p = 0.030). Conclusions: Plasma levels of Sertraline, Citalopram and Escitalopram were more frequently in range in late pregnancy when compared to other drugs. Drug plasma concentrations do not strictly correlate with worse perinatal outcomes, but with possible differences between the different drugs.